THE EFFECT OF BUDGETARY GOAL CHARACTERISTICS ON THE EFFECTIVENESS OF BUDGET CONTROL: WITH KNOWLEDGE OF BUDGETARY AGENCY - DPRD ABOUT BUDGET AS MODERATING VARIABLE (EMPIRICAL STUDY AT REGENCY / MUNICIPALITY OF RIAU - Sheba, Reynelda; Kamaliah, Kamaliah; Agusti, Restu (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
The purpose of this study is to examine the effect of the characteristics of budget objectives: budgetary participation, clarity of budget objectives, budgetary feedback, budget evaluation and budget objective difficulties on the effectiveness of budgetary oversight with knowledge of budget bodies - DPRD as moderating variables.This research is based on a sample of budget body which is a member of council residing in Regency / City DPRD during 2014-2019 period. The method of analysis used in this research is with Simple Linear Regression Analysis model and Moderate Regression Analysis (MRA) by using SPSS 20.00.The results of this study indicate that: 1) budget participation affects the effectiveness of budgetary oversight; 2) budget goal clarity affect the effectiveness of budgetary oversight; 3) budgeting feedback affects the effectiveness of budgetary oversight; 4) budgeting evaluation affects the effectiveness of budgetary oversight; 5) budgeting goal difficulty affect the effectiveness of budgetary oversight; 6) The variable of budget knowledge influences in increasing the relationship of budgetary participation, budget goal clarity, budgeting feedback, budgeting evaluation, budgeting goal difficulty to the effectiveness of budgetary oversight.